«АШЫҚ - НӘЖЕП» ДӘСТАНЫ СЮЖЕТИНИҢ ҮЛГИЛЕРИ ҲӘМ ИЗЕРТЛЕНИЎИ (Түркий версиялары мысалында) - Жепбарова, С. (SCIENCE and SOCIETY, 2020)
The article compares and discusses the research the plot of the folk epos "Ashyk Najep", which is considered an anonymous folk epos, among the Turkic peoples, including the Uzbek, Karakalpak and Turkmenian people. At the same time, the similarities and differences between these three folk versions of the epic are identified and discussed.
Keywords: dastan; baksy (a person who tells epics among the people; epicteller); music skill; typology; plot; version; word